Distinct neural responses to conscious versus unconscious monetary reward cues. Issue 11 (2nd July 2014) - Bijleveld, Erik; Custers, Ruud; Van der Stigchel, Stefan; Aarts, Henk; Pas, Pascal; Vink, Matthijs
Abstract Human reward pursuit is often assumed to involve conscious processing of reward information. However, recent research revealed that reward cues enhance cognitive performance even when perceived without awareness. Building on this discovery, the present functional MRI study tested two hypotheses using a rewarded mental‐rotation task. First, we examined whether subliminal rewards engage the ventral striatum (VS), an area implicated in reward anticipation. Second, we examined differences in neural responses to supraliminal versus subliminal rewards. Results indicated that supraliminal, but not subliminal, high‐value reward cues engaged brain areas involved in reward processing (VS) and task performance (supplementary motor area, motor cortex, and superior temporal gyrus). This pattern of findings is striking given that subliminal rewards improved performance to the same extent as supraliminal rewards. So, the neural substrates of conscious versus unconscious reward pursuit are vastly different—but despite their differences, conscious and unconscious reward pursuit may still produce the same behavioral outcomes. Hum Brain Mapp 35:5578–5586, 2014. © 2014 Wiley Periodicals, Inc.